1990
DOI: 10.1093/jac/25.4.621
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the inoculum effect of antibiotics in the outcome of experimental infections caused by Escherichia coli

Abstract: The minimum dosage of antibiotics that reduced mortality in bacteraemic rats inoculated with two different Escherichia coli isolates was determined in an attempt to study the therapeutic importance of the inoculum effect. Low mortality rates (0-5%) at 48 h were obtained when antibiotics with minimal or no inoculum effect (ampicillin, cefuroxime, cefoxitin and gentamicin) were administered to yield serum levels 5 to 14 times the MIC, while antibiotics with a pronounced inoculum effect (piperacillin, cefotaxime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…One can argue that this was due to an inoculum effect. However, this cannot in itself explain the failure of the drug; there are many reasons why the effect of a drug on a highly complex process of infection might be much more evident at a low than a high inoculum (11,36).…”
Section: Resultsmentioning
confidence: 99%
“…One can argue that this was due to an inoculum effect. However, this cannot in itself explain the failure of the drug; there are many reasons why the effect of a drug on a highly complex process of infection might be much more evident at a low than a high inoculum (11,36).…”
Section: Resultsmentioning
confidence: 99%
“…25 There have been other in vitro and animal studies that support the inoculum effect. [26][27][28] Likewise, MPC increases with bacterial density because of the inoculum effect. 29 Thus, antibiotic MPCs determined on agar plates are likely to be higher than the standard low-inoculum antibiotic MIC against the least susceptible single-step mutant-that is, MPC should be regarded as the actual MIC rather than the theoretically defined standard low-inoculum MIC against the least susceptible single-step mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier recommenda- tions (5, 7) indicate that a peak-to-MIC ratio of 4 to 10 is required for the maximal bactericidal effects of beta-lactam antibiotics. By using a rat model of E. coli peritonitis, it was shown that piperacillin, cefotaxime, and aztreonam prevented mortality when peak concentrations in serum exceeded the MIC by a factor of 60 to greater than 1,000 (23). This group of antibiotics was shown to have a pronounced inoculum effect with the organism.…”
Section: Discussionmentioning
confidence: 99%
“…The explanations for the observed inoculum effect have not yet been defined. One explanation is that an organism may be less susceptible when it is present in large numbers because of the combined production of 1-lactamases (2,20), or, alternatively, preferential affinity for some penicillin-binding proteins may be involved (23).…”
Section: Discussionmentioning
confidence: 99%